2020
DOI: 10.31729/jnma.5033
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction in Patients with Abnormal Uterine Bleeding in a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Abnormal uterine bleeding is a common gynecological presentation, accounting forat least 20% of all new outpatient visits. It has been recognized that thyroid dysfunction may haveprofound effects on the female reproductive system. Both hypothyroidism and hyperthyroidism areassociated with a variety of changes, including delayed onset of puberty, anovulatory cycles, andabnormally high fetal wastage. Hence, this study was conducted to know the thyroid status of thepatient with abnormal uterine blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 10 publications
3
8
0
3
Order By: Relevance
“…Hypothyroidism is generally known to cause heavy and irregular menstrual bleeding and hyperthyroidism is generally associated with hypo, oligo and amenorrhoea. 1 Our finding is similar to studies done in Nepal and India where researchers also found majority of AUB cases associated with euthyroidism followed by hypothyroidism, Subedi, et al 10 found 89.3% cases were euthyroid and 9.3% hypothyroid; Thakur, et al 11 found 84.9% as euthyroid and 13.9% hypothyroid; Kattel, et al 4 found 80% cases euthyroid and 11.1% as subclinical hypothyroid; Bhavani, et al 12 found 81% cases as euthyroid and 10% as subclinical hypothyroid; Gowri M, et al 13 found 77.6% cases as euthyroid and 17.6% cases as hypothyroid. In contrast according to Ajmani, et al 14 44% of the patients with menstrual disorder had thyroid disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Hypothyroidism is generally known to cause heavy and irregular menstrual bleeding and hyperthyroidism is generally associated with hypo, oligo and amenorrhoea. 1 Our finding is similar to studies done in Nepal and India where researchers also found majority of AUB cases associated with euthyroidism followed by hypothyroidism, Subedi, et al 10 found 89.3% cases were euthyroid and 9.3% hypothyroid; Thakur, et al 11 found 84.9% as euthyroid and 13.9% hypothyroid; Kattel, et al 4 found 80% cases euthyroid and 11.1% as subclinical hypothyroid; Bhavani, et al 12 found 81% cases as euthyroid and 10% as subclinical hypothyroid; Gowri M, et al 13 found 77.6% cases as euthyroid and 17.6% cases as hypothyroid. In contrast according to Ajmani, et al 14 44% of the patients with menstrual disorder had thyroid disorders.…”
Section: Discussionmentioning
confidence: 96%
“…A disturbance of the hypothalamic-pituitary function is a less common cause. Additionally, other hormonal disbalances may be accompanied by anovulatory bleeding, such as diseases of the thyroid gland (hypothyroidism, hyperthyroidism), diseases of the adrenal glands, and diabetes mellitus [27,28]. Hyperprolactinemia and elevated levels of cortisol (Cushing's syndrome) can also lead to anovulation.…”
Section: Ovulatorna Disfunkcijamentioning
confidence: 99%
“…Hyperprolactinemia and elevated levels of cortisol (Cushing's syndrome) can also lead to anovulation. Less frequently, the causes can be eating disorders (anorexia, bulimia), chronic disease, alcoholism, drug abuse, and stress [4,27,28].…”
Section: Ovulatorna Disfunkcijamentioning
confidence: 99%
See 2 more Smart Citations